Career Guidance System Using Machine Learning - Panthee, Subiddhya; Rajkarnikar, Sudikshya; Begum, Rabiya (Journal of Advanced College of Engineering and Management, 2023)
Career Guidance System is important for students going through academic and pursuing courses to access their capabilities and identify their interests. This paper mainly concentrates on career guidance through personality prediction. It helps them decide which job role suits the best based on their performance and other evaluations. The system will predict the Big Five personality, and VAK learning type of the users through data collected from web-based questionnaires. The system recommends different career choices based on their answers. Machine learning algorithms will be used to check the performance of the system and validate the result.